Graft Copolymers of Polysaccharide: Synthesis Methodology and Biomedical Applications in Tissue Engineering - Singh, Arun K.; Malviya, Rishabha (Current Pharmaceutical Biotechnology, 2023)
A polymer is a macromolecule that has a significant number of repeating units. It is possible to modify the architecture of a polymer via grafting, bridging, mixing, or generating composites. There are several uses for using natural polymers in culinary and medicinal applications. Polymeric materials became appealing because of their low density and ability to incorporate properties of their constituent constituents. High-energy accelerated electrons from the plasma induce chemical bond breaking in the polymeric structure, resulting in the generation of macromolecule radicals and graft copolymerization. Polymer grafting has become an important aspect of the formulation development process. When polymer functional groups are changed, a wide variety of desirable and unwanted properties can be added or removed. It can be concluded from the findings of the literature survey that graft copolymers of polysaccharides have significant biomedical applications including drug delivery and tissue engineering applications.
Keywords: biomedical application